Bulldaggers, Pansies, and Chocolate Babies Performance, Race, and Sexuality in the Harlem Renaissance - Wilson, James (University of Michigan Press, 2010)
Bulldaggers, Pansies, and Chocolate Babies shines the spotlight on historically neglected plays and performances that challenged early twentieth-century notions of the stratification of race, gender, class, and sexual orientation. On Broadway stages, in Harlem nightclubs and dance halls, and within private homes sponsoring rent parties, African American performers of the 1920s and early 1930s teased the limits of white middle-class morality. Blues-singing lesbians, popularly known as "bulldaggers," performed bawdy songs; cross-dressing men vied for the top prizes in lavish drag balls; and black and white women flaunted their sexuality in scandalous melodramas and musical revues. Race leaders, preachers, and theater critics spoke out against these performances that threatened to undermine social and political progress, but to no avail: mainstream audiences could not get enough of the riotous entertainment.